Evaluación económica de la producción y comercialización del cultivo de cacao (Theobroma cacao L.) en l zona de Quevedo. - Cevallos Avilés, Rafael Colon (2013)
This research was conducted in the Quevedo, in 2012. Its main objective was the evaluation of the production, marketing and profitability of 3235 hectares of cocoa in the Quevedo. The area planted to cocoa Quevedo and his power base is approximately 3.235 hectares, they are distributed in different areas such as; 23.31% La Esperanza, San Carlos 26.83% and ways to Buena Fe 25.47% and 24.39% the joint with , consisting of an estimated 626 producers. For crop management method is used not modernized since the characteristics of the soils are suitable for this crop and require no irrigation facilities due to soil moisture. The 66.3% has been determined to be technically advanced crops and 34% traditional. Tillage applied were the following; pruning, and harvesting. Among the work phytosanitary used are the following: control of pests, diseases and fertilization. The marketing of cocoa producer is focused directly at the collection centers nearest and exporters in the region. The profitability of growing cocoa semitecnificado research for this period was 1.15 dollars, which determined that for every dollar spent you get a profit of 0.15 cents. In the case of traditional crop was 0.93 which states that for every dollar invested loses 7 cents. Semitecnificado Cash flow is ($ 1323.03) and the traditional ($ 1448.05) for the first year, the second year you get $ 742.62 for $ 217.62 semitecnificado and for the traditional. This results in an internal rate of return (IRR) of 17%, a Net Present Value (NPV) of $ 92.93 for the case of crop semitecnificadoy an Internal Rate of Return (IRR) of -9.21%, a Net Present Value (NPV) ($ 500.17) for the case of traditional culture.